Perceptions Of Human Resources Managers On - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Telecommuting concept hos been a new phehomenon /01 11)051 of Mithrysion firms, especially Or human resource managers. Further. the drive toleords promoting the telcconnnitting concept need ro he done as port of representing their tirm's stand ou the relecommuting concept. The propose of this paper is fo e_splore the level ()I oeceptonce r,f' the telecommuting concept by the . Ir Is'elS diSCOVCrell that high percentage of